2016
DOI: 10.1016/j.jssr.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: A Critical Analysis of Race in the Social Studies Classroom: A Review of Doing Race in Social Studies Critical Perspectives

Abstract: The quote "Black lives matter, all lives matter, well cops lives matter too, so why don't we just drop the qualifier and say that lives matter and take that to the bank," was stated by Harris County, Texas Sheriff Ron Hickman after the slaying of a suburban Houston sheriff officer. Race has been a critical topic of interest for centuries. It has heightened in recent years due to current events in places such as New York City, Cleveland, Baltimore, and other cities across America. These events are the root caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…However, the degree to which racism was presented as inconvenience as opposed to a structuring mechanism with material implications that prevent humanity from progressing is debatable (Leonardo, 2014). The often-benign projection of racism is evident in the research that focused on CRT’s critique of liberalism and colorblind ideology (Chandler, 2010; Choi, 2016; Crowley, 2013; Demoiny, 2017, 2018; Martell & Stevens, 2017a, 2017b, 2018) as mainly told through White preservice teachers’ dis-ease (Marshall et al, 2016) towards matters of race. The conclusions we draw here regarding how the centrality of racism is taken up as ideological is evident in 24 of the 59 studies (41%), which we themed as dealing with racial ideology and beliefs towards teaching and learning race.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degree to which racism was presented as inconvenience as opposed to a structuring mechanism with material implications that prevent humanity from progressing is debatable (Leonardo, 2014). The often-benign projection of racism is evident in the research that focused on CRT’s critique of liberalism and colorblind ideology (Chandler, 2010; Choi, 2016; Crowley, 2013; Demoiny, 2017, 2018; Martell & Stevens, 2017a, 2017b, 2018) as mainly told through White preservice teachers’ dis-ease (Marshall et al, 2016) towards matters of race. The conclusions we draw here regarding how the centrality of racism is taken up as ideological is evident in 24 of the 59 studies (41%), which we themed as dealing with racial ideology and beliefs towards teaching and learning race.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular focus amongst the articles analyzed was the teaching of race, as 23 of the articles analyzed maintained this focus. Of these articles, over half (12) examined how teachers engaged their students in topics of race and racism (Chandler, 2009; Ender, 2018; Griffin & James, 2018; Martell, 2013, 2016; Martell & Stevens, 2017a, 2017b, 2018; Masta, 2016; Noboa, 2013; Rodríguez, 2018, 2019); 5 articles offered conceptual/theoretical analyses for social studies teachers, teacher educators, and researchers (Chandler, 2010; Chandler & McKnight, 2009; Daniels, 2011; L. King, 2017; Lintner, 2004); 2 articles provided lesson plans for practitioners (Bolgatz & Crowley, 2015; Hawkman & Castro, 2017); 2 examined teacher educators who focus on race (Demoiny, 2018; Vasquez, 2018); 1 examined the experiences of teachers (Choi, 2016); and 1 article analyzed a schoolwide Black history program (Bery, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the history of race and racism in the U.S. is overwhelmingly absent or glossed over in many textbooks in favor of narratives of racial progress, leaving social studies educators to determine if and how to supplement textbooks' narratives of race and racism. Their work suggested that if teaching materials are selected based on critical race theory principles such ascounter-storytelling, the social studies curriculum has tremendous opportunity to position students for examining historical racism and critiquing the prevalence of racism today (Chandler, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, testimonial stories (Boler, 1997, 1999) were presented in the form of filmic counter-narratives of the U.S. Civil Rights Movement. From a critical race theory perspective, counter-narratives demonstrate that racism is a systematic approach to oppression, central to everyday life in the U.S., and maintained as the norm through power and privilege held by the dominant group (Chandler, 2010). While Barton and Levstik's (2004) concept of perspective recognition has been widely implemented across social studies research, Boler's framework for empathy has not been used in elementary social studies education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation